CIP: an alternative career guidance model to improve self-understanding and work understanding for deaf students - Endang Pudjiastuti Sartinah; Esa Nur Wahyuni; Eryana Fatimasari Retno Budiati (Jurnal Konseling dan Pendidikan, 2023)
The Cognitive Information Processing (CIP) career guidance model is an approach that emphasizes the reconstruction of the mind to achieve self-understanding and understanding of work.  This research examines the CIP career guidance model to improve self-understanding and work understanding in deaf students. This research uses a single-subject design with a pretest-posttest on 12 deaf students in Indonesia. Data collection uses the self-understanding and work understanding Instrument developed by researchers, intervention workbooks, observation instruments, and interviews. Data analysis of this study using non-parametric statistics with the Wilcoxon Test. The results showed that CIP, a career guidance model for deaf students, can improve the knowledge and skills of self-understanding and work understanding. Thus, CIP can be used as a career guidance model for deaf students to improve their self-understanding and work understanding.